Effect of Calendering on Electrode Wettability in Lithium-Ion Batteries - Sheng, Yangping; Fell, Christopher R.; Son, Yong Kyu; Metz, Bernhard M.; Jiang, Junwei; Church, Benjamin C. (Frontiers in Energy Research, 2014)
Controlling the wettability between the porous electrode and the electrolyte in lithium ion batteries can improve both the manufacturing process and the electrochemical performance of the cell. The wetting rate, which is the electrolyte transport rate in the porous electrode, can be quantified using the wetting balance. The effect of the calendering process on the wettability of anode electrodes was investigated. A graphite anode film with an as-coated thickness of 59 μm was used as baseline electrode film and was calendered to produce films with thickness ranging from 55 to 41 µm. Results show that wettability is improved by light calendering from an initial thickness of 59 μm to a calendered thickness of 53 μm where the wetting rate increased from 0.375 to 0.589 mm/s0.5. Further calendering below 53 µm resulted in a decrease in wetting rates to a minimum observed value of 0.206 mm/s0.5 at a calendered thickness of 41 μm. Under the same electrolyte, wettability of the electrode is controlled to a great extent by the pore structure in the electrode film which includes parameters such as porosity, pore size distribution, pore geometry and topology. Relations between the wetting behavior and the pore structure as characterized by mercury intrusion and electron microscopy exist and can be used to manipulate the wetting behavior of electrodes.